Ectoine-Containing Inhalation Solution versus Saline Inhalation Solution in the Treatment of Acute Bronchitis and Acute Respiratory Infections: A Prospective, Controlled, Observational Study. (31st January 2019) - Tran, Binh-Hai; Dao, Van-Anh; Bilstein, Andreas; Unfried, Klaus; Shah-Hosseini, Kija; Mösges, Ralph
Abstract : Purpose . This study investigated an inhalation solution containing ectoine, a bacterial-derived extremolyte, for the treatment of acute bronchitis and acute respiratory infections in comparison with saline inhalation solution. Methods . This prospective, controlled, observational study comprised an inclusion visit (day 1), a final visit (day 7), and a follow-up questionnaire (day 17). The treatment itself was administered from day 1 to day 7. The Bronchitis Severity Score, patients' general health, general effectiveness of the treatment, tolerability, and adverse events were compared between two groups. Results . In total, 135 patients were recruited; 79 patients received ectoine inhalation solution and 56 saline inhalation solution. After treatment, symptom scores decreased significantly in both groups ( P < 0.05); the reduction in symptom scores was slightly greater in the ectoine group than in the saline group. The first significant reduction in symptom scores ( P < 0.05) occurred earlier in the ectoine group than in the saline group. The differences in the area under the curve for the symptoms of dyspnea and auscultation findings were significant in favor of ectoine ( P < 0.05). After treatment, more patients and physicians in the ectoine group assessed their or their patients' condition as "completely recovered" or "greatly improved" than those in the saline group. Almost all patients and physicians assessed the tolerability of both treatments as "good" or "very good". Conclusions . Ectoine inhalation solution seems to be slightly more effective than saline inhalation solution for the treatment of acute bronchitis and acute respiratory infections.